2022
DOI: 10.51329/mehdioptometry153
|View full text |Cite
|
Sign up to set email alerts
|

Changes in accommodation with visual fatigue among digital device users

Abstract: Background: Visual fatigue is categorized as a complex phenomenon that decreases visual performance. The aim of the present study was to assess changes in accommodation at different levels of visual fatigue among students of a Malaysian private university using digital devices. Methods: In this cross-sectional study, students regardless of sex and ethnicity were included. A comprehensive eye examination was performed. After estimating the level of visual fatigue, the amplitude of accommodation (AA), acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…This happens mainly because of prolonged usage of inappropriate computer workstations [ 15 , 52 ]. In addition, due to improper workstations, employees are working with heightened muscle tension and mental fatigue which also lead to MSDs [ 3 , 6 , 17 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This happens mainly because of prolonged usage of inappropriate computer workstations [ 15 , 52 ]. In addition, due to improper workstations, employees are working with heightened muscle tension and mental fatigue which also lead to MSDs [ 3 , 6 , 17 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another similar research found that itchy eyes and teary eyes were the most prevalent visual complaints among computer users [ 47 ]. The presence of bright lighting and glare in the working environment leads to eye strain and difficulty in seeing objects on computer screens [ 6 , 23 ]. A previous study found that visual symptoms were attributed to average daily computer-related work hours, and visual symptoms were higher with increased light glaring in computer workstation areas [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations